Tithonia diversifolia, its possibilities in cattle rearing systems - Ruiz, Tom?s E.; Febles, Gustavo; Galindo, Juana; Sav?n, Lourdes; Chongo, Bertha; Cino, Delia Mar?a; Alonso, Jatnel; Mart?nez, Y.; Guti?rez, Delf?n; Crespo, Gustavo; Mora, Luis Marino; Scull, Idania; et al. (Cuban Journal of Agricultural Science, 2014)
Information about the performance of different plant materials of Tithonia diversifolia collected in the central-western region of Cuba is offered. A technology for biomass production, cut performance, grazing and for its use in the biological and physiological performance of animals used in the cattle development is presented. Plants materials destined to animal feeding are also presented. They offer options for biomass production in cut (5, 10, 16 and 23) or grazing (3, 5, 10, 23 and 24). In calves, the inclusion of Tithonia forage meal allows gains over 700 g/animal/d, with liveweight superior to 100 kg at four months of age and good health. Up to 50 % of the protein material of the concentrate may be substituted by meal of this plant to feed lactating goat kids and reach daily weight gain of 60-90 g. The substitution of feedstuff by 5 and 10 % of Tithonia foliage meal provides acceptable gains in the weaning (201 g/animal/d) and growing-fattening stage (528 g/d), for the small and middle swine production. The use of Tithonia foliage meal contributes to improve the health of the animals consuming it. This offers the possibility of having other shrubs to be used in silvopastoral systems. Key words: green materials, biomass production, biological and physiological performance of calves, goats and pigs.